1980
DOI: 10.1083/jcb.86.3.881
|View full text |Cite
|
Sign up to set email alerts
|

Stacking in lipid vesicle-tubulin mixtures is an artifact of negative staining.

Abstract: Multilamellar stacking seen in negatively stained lipid vesicle-tubulin mixtures has been attributed to lipid-protein interactions (Caron, J . M., and R. D . Berlin, 1979, 1. Cell Biol. 81 :665-671) . We show that this stacking is produced by the phosphotungstic acid used for staining, independent of the presence of tubulin in the sample . The morphology of negatively stained single bilayer vesicles obtained from dimyristoyl phosphatidylcholine or egg lecithin is specifically dependent upon the choice of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
3
27
0
Order By: Relevance
“…[169] Other studies showed that the stain could introduce distortions to some molecules, such as general aggregation, molecular dissociation, and flattening. [167,170,171] For example, a common artifact due to negative staining of lipid-related proteins is that particles stacked and packed together into a structure called a rouleaux. [163,172176] Recently, an optimized negative-staining (OpNS) method [177179] was proposed via a refined conventional protocol (Figure 10).…”
Section: Advances In Et For Soft-materials and Biomaterials Researchmentioning
confidence: 99%
“…[169] Other studies showed that the stain could introduce distortions to some molecules, such as general aggregation, molecular dissociation, and flattening. [167,170,171] For example, a common artifact due to negative staining of lipid-related proteins is that particles stacked and packed together into a structure called a rouleaux. [163,172176] Recently, an optimized negative-staining (OpNS) method [177179] was proposed via a refined conventional protocol (Figure 10).…”
Section: Advances In Et For Soft-materials and Biomaterials Researchmentioning
confidence: 99%
“…NS-EM also delivers images that contain high SNR, and an intermediate (near a nanometer) resolution [3] for reconstruction of three-dimensional (3D) models [20]. However, certain effects of the heavy-metal stain produce undesirable outcomes due to interactions with the specimen, such as aggregation, molecular dissociation, and artifacts of stacking [4, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…An obvious artifact of lipoprotein structure observed for decades is how the lipoprotein particles regularly present stacking rouleau in NS images [3540]. This is significant in that rouleau formation is absent from serum analysis, native-gel, small-angle scattering, and cryo-EM studies [12, 22, 29, 30, 36, 39, 4144]. Considering that rouleau formation displayed in NS images could lead to inaccurate interpretations of lipoprotein structure and function, a thorough investigation or comparison of the NS protocols used to examine the lipoprotein structure is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional NS, unfortunately, can produce artifacts induced by stain-protein interactions, such as general aggregation, molecular dissociation, flattening and stacking 8,21,22 . For lipid related proteins, such as lipoproteins 16,23–30 , a common artifact results in particles that are stacked and packed together into a rouleaux (Figure 1) 3136 .…”
Section: Introductionmentioning
confidence: 99%
“…For lipid related proteins, such as lipoproteins 16,23–30 , a common artifact results in particles that are stacked and packed together into a rouleaux (Figure 1) 3136 . Many lipoprotein studies, such as nondenaturing polyacrylamide gradient gel electrophoresis, cryo-EM studies 13,29,37–40 , mass spectrometry 39,41 , and small angle X-ray diffraction data 42 all show lipoprotein particles are isolated particles instead of naturally stacked together forming a rouleaux 21,29,30,35,4245 . The observation of rouleaux formation by conventional NS is possibly caused by dynamic interactions between lipoproteins composed of apolipoproteins (apo) and phospholipids that are structurally flexible in solution 13,29,30,4649 and sensitivity to the standard NS protocol.…”
Section: Introductionmentioning
confidence: 99%